2004
DOI: 10.5194/angeo-22-1421-2004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of absorbing aerosols on the simulation of climate over the Indian region in an atmospheric general circulation model

Abstract: Abstract. The impact of anthropogenic absorbing aerosols (such as soot) on the climate over the Indian region has been studied using the NCMRWF general circulation model. The absorbing aerosols increase shortwave radiative heating of the lower troposphere and reduce the heating at the surface. These effects have been incorporated as heating of the lower troposphere (up to 700 hPa) and cooling over the continental surface based on INDOEX measurements. The heating effect is constant in the pre-monsoon season and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Many models seem to have a tendency to get locked into either the oceanic or the continental TCZ (Gadgil and Sajani 1998). & Emissions of scattering and absorbing aerosols in the region are found to affect the monsoon climate (Chakraborty et al 2004). The uncertainty in the level of these emissions and the ability to model their impact on the monsoon are a problem (Sajani et al 2012;Turner and Annamalai 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many models seem to have a tendency to get locked into either the oceanic or the continental TCZ (Gadgil and Sajani 1998). & Emissions of scattering and absorbing aerosols in the region are found to affect the monsoon climate (Chakraborty et al 2004). The uncertainty in the level of these emissions and the ability to model their impact on the monsoon are a problem (Sajani et al 2012;Turner and Annamalai 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Menon et al () found a reduction of precipitation over north Indian Ocean when an atmospheric GCM was forced with radiative effects of carbonaceous aerosols over south Asian region. Chakraborty et al () used an atmospheric GCM with aerosol forcing obtained from INDOEX (Indian Ocean Experiment) field campaign to show that the change in precipitation during monsoon season due to aerosols depend on the cumulus scheme used in the model. The impact of black carbon aerosols on tropical convection and climate has been studied by Wang (, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, during a break, aerosol concentration builds up in central and north India through local emissions and long range transports while the north Indian Ocean remains relatively pristine. As a large fraction of these aerosols is of absorbing type (Menon 2004;Chakraborty et al 2004;Bollasina et al 2008), they would cool the surface but warm the atmospheric layer between 1 and 3 km. Such warming of the lower atmosphere over central and north India and lack of it over the north Indian Ocean would lead to a north-south temperature gradient at this level and convergence of moisture to central and north India.…”
Section: Introductionmentioning
confidence: 99%